Discovery of anti-infective compounds against Mycobacterium marinum after biotransformation of simple natural stilbenes by a fungal secretome - Nitschke, Jahn; Huber, Robin; Vossio, Stefania; Moreau, Dimitri; Marcourt, Laurence; Gindro, Katia; Queiroz, Emerson F.; Soldati, Thierry; Hanna, Nabil (Frontiers in Microbiology, 2024)
Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis, remains a serious threat to human health worldwide and the quest for new anti-tubercular drugs is an enduring and demanding journey. Natural products (NPs) have played a significant role in advancing drug therapy of infectious diseases. This study evaluated the suitability of a high-throughput infection system composed of the host amoeba Dictyostelium discoideum (Dd) and Mycobacterium marinum (Mm), a close relative of Mtb, to identify anti-infective compounds. Growth of Dd and intracellular Mm were quantified by using luminescence and fluorescence readouts in phenotypic assays. The system was first benchmarked with a set of therapeutic anti-Mtb antibiotics and then used to screen a library of biotransformed stilbenes. Our results confirmed both efficacy of established antibiotics such as rifampicin and bedaquiline, with activities below defined anti-mycobacterium susceptibility breakpoints, and the lack of activity of pyrazinamide against Mm. The screening revealed the promising antiinfective activities of trans-δ-viniferins and in particular of two compounds 17 and 19 with an IC50 of 18.1 µM, 9 µM, respectively. Both compounds had no activity on Mm in broth. Subsequent exploration via halogenation and structure-activity relationship studies led to the identification of derivatives with improved selectivity and potency. The modes of action of the anti-infective compounds may involve inhibition of mycobacterial virulence factors or boosting of host defense. The study highlights the potential of biotransformation and NP-inspired derivatization approaches for drug discovery and underscores the utility of the Dd-Mm infection system in identifying novel anti-infective compounds.This study underscores the significance of leveraging natural product-inspired approaches and innovative infection models in search for novel anti-infective compounds. By benchmarking and employing highthroughput Dictyostelium discoideum-Mycobacterium marinum infection system on a small, focused library of natural product derivatives, the study identified trans-δ-viniferins as a promising anti-infective scaffold against M. marinum, opening potential therapeutic avenues for combating tuberculosis. The findings highlight the value of exploring nature-inspired chemistry for drug discovery and addressing global health challenges.